2017
DOI: 10.3389/fmicb.2017.01936
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gut Microbiota on Cardio-Metabolic Parameters and Immunity in Coronary Artery Disease Patients with and without Type-2 Diabetes Mellitus

Abstract: Gut microbiota composition has been reported as a factor linking host metabolism with the development of cardiovascular diseases (CVD) and intestinal immunity. Such gut microbiota has been shown to aggravate CVD by contributing to the production of trimethylamine N-oxide (TMAO), which is a pro-atherogenic compound. Treg cells expressing the transcription factor Forkhead box protein P3 (FoxP3) play an essential role in the regulation of immune responses to commensal microbiota and have an atheroprotective role.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 46 publications
9
59
0
2
Order By: Relevance
“…Our meta‐analysis of continuous variables of the relationship between TMAO concentration and DM risk included 5330 participants from five studies in which all samples were plasma. We calculated the SMD of TMAO levels in DM and non‐DM populations after unit conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Our meta‐analysis of continuous variables of the relationship between TMAO concentration and DM risk included 5330 participants from five studies in which all samples were plasma. We calculated the SMD of TMAO levels in DM and non‐DM populations after unit conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that the abundance of endosymbionts and other bacteria inside the bodies of different spider species was different. It is well‐known that research on gut bacteria of invertebrate and vertebrate animals is increasing because of their potential function on their hosts (Berasategui et al., ; Sanchez‐Alcoholado et al., ; Smith, Srygley, Healy, Swaminath, & Mueller, ). Spiders have a special feeding mode.…”
Section: Discussionmentioning
confidence: 99%
“…Egg yolks, milk, dairy products, organ and muscle meats, and seafood such as mollusks, crustaceans, and fish are major dietary sources of TMAO and its precursors, although whether circulating TMAO is affected by dietary source needs to be further evaluated . There are numerous studies regarding the association between TMAO and biomarkers or risk factors of CVD, increased insulin resistance, impaired glucose metabolism, and metabolic syndrome . Possible suggested mechanisms about the association between TMAO and cardiovascular risk factors could be increased cholesterol accumulation in macrophages and in foam cells of artery walls or increased human platelet hyper‐responsiveness and potential of thrombosis in higher TMAO concentrations.…”
Section: Discussionmentioning
confidence: 99%